Urgensi dan Peran Program Studi Komunikasi Penyiaran Islam Dalam Standarisasi Khatib - A. Syarifudin; Siti Hajariyah (Fakultas Dakwah dan Komunikasi, Universitas Islam Negeri, Raden Fatah Palembang, 2019)
Abstract: Standardization of the preacher has two dimensions that lead to the agree and contradiction of the ulama, the muballigh and da'i. As an effort to realize good competencies and qualifications for the preacher is a very positive thing so that the stake holders become enlightened. If this is desired from standardization, it will be a hope and necessity for all Muslims. Through gathering forums activities can be improved on preacher capacity. However, if standardization is used as an effort to select, assessing credibility regarding the grade of study taken, or limiting the material of the sermon, then this is contrary to the existence of the preacher and the existence of mosques in Indonesia. Because, mosques that stand in this country are self-help communities and those who choose people to become preacher are selection based on their moral size and religiosity qualifications. Therefore, based on this research, the standardization of preacher is not needed at this time, and Islamic Broadcasting Communication Study Program is deemed not necessary to involve itself in the issue of preacher standardization. Keywords: Standardization, preacher competence